Play safe with Sisimpur: an evaluation of a child injury prevention intervention in Bangladesh. Issue 1 (16th November 2020) - Foulds, Kim; Peng, David; Zaidi, Samera
Abstract: For children under the age of 18 in Bangladesh, road traffic injuries, drowning, animal bites, poisonous substances, falls, burns, and electrocutions and fire-related burns pose significant and serious risk and are a leading cause of mortality, especially in rural areas. Despite this, there is limited evidence of what works to increase children's knowledge of injury prevention and decrease incidents of unintentional injury. This study addresses this gap by presenting findings from an evaluation of Play Safe with Sisimpur. Leveraging the popularity of Sisimpur, the Bangladeshi co-production of Sesame Street, Play Safe with Sisimpur employed a school-based child-to-child and adult-to-adult mentorship model, designed to improve injury prevention knowledge and promote behavior change. Child survey results demonstrate a significant change between baseline and end line in the knowledge of children related to injury prevention and treatment for burns, electrocution, falls, household hazards, playing safe, road traffic injuries, and water safety. Adult mentee survey results demonstrate a significant change between baseline and end line in the knowledge of adult mentees related to injury prevention and treatment of animal injuries, burns, falls, household hazards, and road traffic injuries.